2008
DOI: 10.1063/1.3032911
|View full text |Cite
|
Sign up to set email alerts
|

Valence band offset of the ZnO/AlN heterojunction determined by x-ray photoemission spectroscopy

Abstract: The valence band offset of ZnO/AlN heterojunctions is determined by high resolution x-ray photoemission spectroscopy. The valence band of ZnO is found to be 0.43Ϯ 0.17 eV below that of AlN. Together with the resulting conduction band offset of 3.29Ϯ 0.20 eV, this indicates that a type-II ͑staggered͒ band line up exists at the ZnO/AlN heterojunction. Using the III-nitride band offsets and the transitivity rule, the valence band offsets for ZnO/GaN and ZnO/InN heterojunctions are derived as 1.37 and 1.95 eV, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
43
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(50 citation statements)
references
References 34 publications
5
43
0
2
Order By: Relevance
“…As far as we are concerned here with rather low In-content, typically x<35%, our results show that In x Al 1-x N/ZnO and In x Ga 1-x N/ZnO are both type II heterostructures. Our results are consistent with ab-initio those reported by Van de Walle et al [4], and with recent photo-emission spectroscopy ones [10,11]. They also agree very well with those given by Yang et al [3] which have shown the strong anisotropy of the energy band lineup at the interface of an InN/ZnO heterostructure.…”
Section: Energy Band-offsetssupporting
confidence: 95%
“…As far as we are concerned here with rather low In-content, typically x<35%, our results show that In x Al 1-x N/ZnO and In x Ga 1-x N/ZnO are both type II heterostructures. Our results are consistent with ab-initio those reported by Van de Walle et al [4], and with recent photo-emission spectroscopy ones [10,11]. They also agree very well with those given by Yang et al [3] which have shown the strong anisotropy of the energy band lineup at the interface of an InN/ZnO heterostructure.…”
Section: Energy Band-offsetssupporting
confidence: 95%
“…Indeed, from direct measurements, measurements of valence band offsets (allowing band alignment relative to the CNL), and theoretical calculations [63,135,[163][164][165][166][167], the CNL has been found to occur above the CBM across the TCOs, as summarized in Fig. 11.…”
Section: Overriding Explanation?mentioning
confidence: 99%
“…1(d) and (f). The VBM positions in the VB spectra were determined by linear extrapolation of the leading edges of VB spectra to the base lines in order to account for the finite www.pss-b.com instrument resolution [15,16]. The scatter of the data with respect to the fit are estimated as uncertainty in VBM positions of less than 0.04 eV, which are also estimated from fitting with different parameters.…”
mentioning
confidence: 99%